2021
DOI: 10.1109/access.2021.3089367
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Distribution of Suspended Sediment Concentration in Lakes Based on Satellite Remote Sensing and Internet of Things

Abstract: The measurement of the concentration of suspended sediment in a water body is a very important content in the observation of hydrological elements, and it is also one of the important parameters for calculating the sediment resuspension flux. In order to accurately predict the distribution of lake sediment, this paper uses satellite remote sensing data to invert the suspended sediment concentration. The key to the quantitative inversion is the atmospheric correction and the suspended sediment concentration inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…The chosen linear model is an inversion algorithm tailored for high turbidity waters in Hangzhou Bay, with verified feasibility. The inversion of the distribution of suspended matter concentration in Hangzhou Bay is consistent with the distribution of suspended matter concentration in this area in previous studies [46,47].…”
Section: Inversion Model Of the Ssc In The Qiantang Riversupporting
confidence: 90%
See 1 more Smart Citation
“…The chosen linear model is an inversion algorithm tailored for high turbidity waters in Hangzhou Bay, with verified feasibility. The inversion of the distribution of suspended matter concentration in Hangzhou Bay is consistent with the distribution of suspended matter concentration in this area in previous studies [46,47].…”
Section: Inversion Model Of the Ssc In The Qiantang Riversupporting
confidence: 90%
“…For high suspended sediment concentration water, such as Hangzhou Bay, the suspended sediment is sensitive to the red and NIR bands. However, it is not suitable for low suspended sediment concentration water [30,47].…”
Section: Inversion Model Of the Ssc In The Qiantang Rivermentioning
confidence: 99%
“…To better visualize the trend of lake area change, geometric alignment was carried out, using the 2010 remote sensing images as a benchmark for absolute radiation correction and FLASH atmospheric correction was used on the other six phases of images. The main methods for lake water body extraction are the thematic classification method [48,49], linear mixed model, single-band threshold method, and spectral water body index method [30,50,51]. Previous studies, through experimental evaluation of these methods, generally concluded that the traditional normalized difference water body index (NDWI) method is more effective in extracting water body information and can distinguish water body and non-water body information in remote sensing images to the maximum extent, but it is vulnerable to mountain shadows, snow and ice, and mist [31,34,[52][53][54][55][56][57][58].…”
Section: Data Collectionmentioning
confidence: 99%
“…In terms of innovation, this paper is the first to study the sediment content of dammed lakes. With the development of remote sensing for lakes, remote sensing technology has been widely used for highland lake change and sea, estuarine and near-shore, lake suspended sediment monitoring studies, and many mature suspended sediment quantitative remote sensing inversion models have been established [27][28][29][30][31][32][33]. In the study of lake changes, multispectral optical remote sensing images such as Landsat MSS/TM/ETM+/OLI, Gaofen series satellites (GF-1/2), and Sentinel data (Sentine-2) have been used for the monitoring of lake area changes on the Qinghai-Tibet Plateau since the 1970s, among which, the Landsat data series are most widely used because they provide more high-quality free data [34].…”
Section: Introductionmentioning
confidence: 99%
“…Within literature, multiple methods for measuring the sediment concentration within the ocean have been demonstrated. Such efforts include satellite sensing [6], [7] where multiple sensors transfer all the data back to a master controller. Other methods utilise RFID tags [8] but suffer from poor resolution and high power consumption.…”
Section: Introductionmentioning
confidence: 99%